Praktik Pengendalian Internal pada Pengelolaan Keuangan di Lembaga Kemahasiswaan - Septiyan Dwi Anggara (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
Financial fraud cases occur in large as well as small organizations. These, even happen in the Student Council of higher education. This phenomenon calls for the need of adequate internal control. Internal control has been implemented in Student Councils. However, it requires more understanding in the effort to minimize fraud, and for sake of organization sustainability. This study aims to reveal internal control practices in financial management at the Student Council. This study uses a case study method to examine the phenomena. The data were collected by interviewing 5 (five) caretakers of the Student Council. The results of the study reveal that the practice of internal control in financial management has been implemented, but has not been comprehensive. The results of this study are expected to be a consideration to develop internal controls over financial management.